Rekonstruksi Hadits dan Konsep Doublemovement (Telaah Pemikiran Fazlur Rahman sebagai Pembacaan Hadits Kontemporer) - Rajendra Rahmat Ramadhan (KOLONI, 2023)
The study of al-Hadith has been developed by earlier scholars, but over time, thoughts on Hadith have evolved. Fazlur Rahman offered his theory regarding the reconstruction of understanding Hadith, such as the Double Movement. The Double Movement represents his "critical" stance toward contextual readings of Hadith. Rather than viewing Hadith as something sacred, it's critically examined. Certainly, Islamic intellectuals can further formulate this seriously. To what extent one's approach in understanding Hadith can be assessed, whether in transmission or its chain of narration. Rahman firmly stated that Hadith is one of the products of historical past and there's no possibility of flaws in its methodology being accepted by Muslims in the present time. The use of the Double Movement can also contribute to its adaptation in the modern lives of Muslims.